The Implementation of Digital Marketing in Culinary SMEs in Batam Using the SOSTAC Framework - Eryc Eryc; Sylvester Tan; Surya Tjahyadi (Universitas Bandar Lampung (UBL), 2025)
This study examines the implementation of the SOSTAC digital marketing framework and its influence on marketing performance among culinary SMEs in Batam. Using a quantitative explanatory approach, data were collected from 140 SME owners through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that the SOSTAC framework has a strong and significant positive effect on marketing performance, demonstrating that structured planningfrom situation analysis to control enhances sales, customer engagement, market reach, and brand awareness. Unlike previous studies that only explore general digital marketing activities or single-channel strategies, this research provides a comprehensive empirical test of the full SOSTAC framework in the SME culinary sector, which has been largely underexplored.Additionally, this study uniquely examines how resource constraints moderate the SOSTAC performance relationship, offering new insights into how limited budgets, skills, and labor capacity shape the effectiveness of structured digital planning. Although resource constraints such as limited budgets, digital skills, and workforce capacity do not directly affect marketing performance, they significantly moderate the relationship between SOSTAC implementation and performance, weakening its positive impact. The model explains 53.2% of the variance in marketing performance, reflecting moderate explanatory power. The study highlights the importance of structured digital marketing planning while underscoring the need to manage resource limitations effectively to maximize outcomes. The findings offer practical direction for SMEs by highlighting the need to adopt structured digital planningsuch as setting measurable monthly objectives, choosing the most effective social media channels, and consistently monitoring key performance indicators to maximize the benefits of SOSTAC under limited resources